Scaling Access to Contraception for Youth in Urban Slums: The Challenge Initiative's Systems-Based Multi-Pronged Strategy for Youth-Friendly Cities - Krishna Bose; Kim Martin; Kathryn Walsh; Maheen Malik; Paul Nyachae; Morine Lucy Sierra; Albert Bwire; Denis Sama; Tumaini Kiyola; Vanessa Mitchell; Hawa Talla; Josephat Avoce; et al. (Frontiers Media S.A., 2021)
Introduction: More than half of all adolescents globally live in Asia, with India having the largest adolescent population in the world at 253 million. In sub-Saharan Africa, adolescents make up the greatest proportion of the population, with 23% of the population aged 10-19. And these numbers are predicted to grow rapidly-particularly in urban areas as rural youth migrate to cities for economic opportunities. While adolescents and youth are subject to high sexual and reproductive health risks, few efforts have been documented for addressing these in urban settings, especially in poor settlements.Methods: The Challenge Initiative (TCI) is a demand-driven, family planning platform for sustainable scale and impact that lets city governments-in particular urban slums-lead implementation. It is currently active in 11 countries in Africa and Asia. In June 2018, TCI heightened its focus on adolescent and youth sexual and reproductive health (AYSRH) for youth living in urban slums. It now supports 39 city governments. TCI dedicates technical and program support to married (including first-time parents) and unmarried youth ages 15-24 years. Using an innovative coaching model and an online learning platform (TCI University), TCI supports city governments as they implement AYSRH interventions to accelerate the impact of TCI's model for rapid scale.Results: TCI has been assessing the performance of cities implementing its AYSRH approaches using its RAISE tool and has found considerable improvement over two rounds of assessments through TCI coaching and support for adaptation of its high-impact interventions between the first and second round.Conclusions: TCI's AYSRH approach scaled rapidly to 39 cities and multiple urban slums since 2018, using its evidence-based interventions and coaching model. In the context of universal health coverage, TCI has supported segmented demand generation and improved access to quality and affordable contraceptive as well as youth-friendly health services. It provides a menu of interventions for cities to implement for youth-including such approaches as public-private partnerships with pharmacies and quality assurance using quick checklists-along with an innovative coaching model. This approach has facilitated greater access to contraceptive methods of choice for youth.